2021
DOI: 10.1532/hsf.3753
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Risk Assessment for Surgery of Consecutive Cases with Ventricular Septal Rupture: Seeking A Novel and Comprehensive Method

Abstract: Background: Ventricular septal rupture (VSR) is a rare but lethal complication occurring after acute myocardial infarction. The aim of our study was to review the single-center experience of surgery for VSR and seek a comprehensive evaluation process for early mortality. Methods: Patients undergoing surgical repair for postinfarction VSR in our institution retrospectively were evaluated from Jan. 2006 to Dec. 2019. The endpoint of the study was mortality within 30 days after VSR surgery, which was divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Some studies (3,27) have shown that repair of VSR accompanied by CABG can improve prognosis. In this study, the median follow-up time was 4.2 years, and a total of 7 cases (11.9%) died during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (3,27) have shown that repair of VSR accompanied by CABG can improve prognosis. In this study, the median follow-up time was 4.2 years, and a total of 7 cases (11.9%) died during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…European Heart Surgery Risk Assessment System II (EuroSCORE II) is a widely used cardiac surgery scoring system. It can accurately assess preoperative risk, predict in-hospital mortality in postoperative patients, which is essential for providing treatment options and improving quality of care and patient prognosis ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%